Penerapan Sistem Informasi Akuntansi (SIA) Pelayanan Jasa Rawat Inap Pada Rumah Sakit ( Studi pada Rumah Sakit Umum Hermina Pasteur Bandung Kecamatan Cicendo Kota Bandung) - Gunawan, Gun Gun; Purwanti, Meilani (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to determine the application and accuracy of the Accounting Information System for Inpatient Services at Hermina Pasteur General Hospital. The research method used is qualitative descriptive method, where the data obtained comes from the source of the Hermina Pasteur General Hospital profile, organizational structure and inpatient service reports. namely this research was conducted by conducting interview, observation and documentation techniques with employees of RSU Hermina Pasteur. Based on the results of the study, it can be concluded that the accounting information system for inpatient services at Hermina Pasteur General Hospital has used a computerized system in all areas of its scope of activities ranging from information services, patient registration, authorization of transactions, and patient discharge process services have been running smoothly effectively and efficiently and internal control in the inpatient service system has been running well. This is evidenced by the increasing number of patients entering and leaving the hospital and the speed of the data entry process. The application of accounting information systems in hospitals has provided easy access to data and data collection in hospital services. Hermina Pasteur General Hospital has implemented an accounting information system in supporting hospital inpatient services. This is supported by an adequate accounting information system and is evidenced by the system running well and smoothly so that the objectives of the hospital can be achieved properly.